Menurunkan Keluhan Nyeri Pada Tubuh Pekerja Pada Proses Pembersihan Hardware Menggunakan Analisis NBM, RULA, dan Antropometri - Barita, Erwin; Nuryono, Arif (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
The impact of the Covid-19 pandemic has created many new habits, rapid changes in information have made the need for the use of computers and electronic devices important for society and entrepreneurs. PT. RSS is engaged in the procurement of goods, maintenance, telecommunication services and event management. When workers carry out the maintenance process by cleaning hardware devices, non-ergonomic work positions are identified. This working position results in complaints of pain in the worker’s body which results in a reduced number of hardware products being cleaned. Complaints experienced by workers can cause long-term illness and Musculoskeletal Disorders (MSDs). This research was conducted to help workers/technicians when cleaning hardware is more ergonomic. Data collection was carried out by observing the body position of 5 workers while cleaning the hardware. This research begins by identifying problems using the NBM method. Then analyze worker posture using RULA and Anthropometry. The results of the analysis of this study are that work aids are needed so that workers are more ergonomic. The tools needed are to design and make an ergonomic workbench according to the dimensions of the worker’s body. The table measures 167.2 cm long, 104.2 cm high and 73.4 cm wide. Evaluation of the results showed complaints of pain in the workers’ bodies decreased. Complaints of workers’ bodies before using the workbench have a value of 7 or the "Very High" category then drop to 4 or the "Moderate" category using the RULA assessment.